Autoimmune Pancreatitis Accompanied with Recurrence of Bladder Cancer: Difficulty in Diagnosis and Management of Systemic Lesions in a Case with Autoimmune Pancreatitis - Matsubayashi, Hiroyuki; Kimura, Hirokazu; Tobisu, Kenichi; Onishi, Yoshifumi; Moriguchi, Michihisa; Sasaki, Keiko; Ono, Hiroyuki (JOP. Journal of the Pancreas, 2012)
Context A case of autoimmune pancreatitis develops a hepatic metastasis of bladder cancer resected over 5 years before, mimicking a pseudotumor of the liver. Case report A 71-year-old man with a surgical history of bladder cancer (pT4, G2>3, N (+)) later developed autoimmune pancreatitis. Diagnosis of autoimmune pancreatitis was not problematic; however, a variety of systemic disorders appeared after the onset of autoimmune pancreatitis, possibly associated with autoimmune disorder or steroid therapy. These included pancreatic stone attack, septic shock due to ureteral stenosis, and bloody phlegm due to a lung aspergilloma. These events were not easily controlled but were managed with clinical efforts. In the following course, pelvic lymph nodes gradually enlarged and a hepatic mass occurred at 5 years and 6 months after total cystectomy. Several candidates were considered for the hepatic lesion including inflammatory pseudotumor, cholangiocellular carcinoma, and hepatic adenoma. However, percutaneous biopsy confirmed metastasis of the bladder cancer. In general, recurrence after 5 years following cystectomy is extremely rare in cases of pT4 bladder cancer with lymph node metastasis. Conclusions Patients of autoimmune pancreatitis display various problematic scenarios in diagnosis and long-term management, not only for their pancreatic lesions but also for systemic lesions. Image: Histology of percutaneous hepatic biopsy showed urothelial carcinoma.